SEX, EMPLOYMENT STATUS AND THE LABOUR FORCE CONTRIBUTION OF POLYTECHNICS GRADUATES - Arikpo, Abam (European Scientific Journal, ESJ, 2014)
The purpose of this study is to find out the influence of sex, employment status and polytechnics education on labour force contributions of polytechnic graduates. Three null hypotheses were formulated to guide the study. Sixty (60) Polytechnics graduates who were either male, female, unemployed, self-employed, organized private sector employed or government sector employed were selected for the study, through snow balling and convenience sampling techniques. Five (5) Likert type questionnaires were used to collect data from the both male and female polytechnics graduates. Percentages, t-test, and chi-square statistics were used to analyze data collected at 0.05 alpha level. For the men all the three null hypotheses were rejected; while for women only two were, because calculated χ2 was under these hypotheses greater than critical χ2. The result revealed men to make significantly higher contribution to the national labour force than women. It was recommended conscientization and other androgogical methods be used to promote consciousness raising in the women.